Geopolymer concrete incorporating agro-industrial wastes: Effects on mechanical properties, microstructural behaviour and mineralogical phases. (30th September 2020) - Oyebisi, Solomon; Ede, Anthony; Olutoge, Festus; Omole, David
Highlights: Application of both GGBFS and CCA in the production of GPC in ambient curing conditions is attainable. CCA replacement level (up to 40%) exhibited higher mechanical strength than PCC. The intensity of calcium counts in the SEM-EDX micrographs increased with increasing GGBFS content in the mixture. The intensity of silicon counts in the SEM-EDX micrographs increased with increasing CCA content in the mixture. C-A-S-H gels are responsible for higher strengths of GGBFS-CCA based GPC. Abstract: The increasing effects of environmental degradation and global warming owing to the production of Portland cement for uses in the construction industry premise the need for sustainable construction materials. This study, therefore, harnessed corncob ash (CCA) and ground granulated blast furnace slag (GGBFS) for the production of geopolymer concrete (GPC) at ambient curing conditions. Corncob was dehydroxylated at 600 °C and partially used as replacement for GGBFS at 0%, 20%, 40%, 60%, 80%, and 100%. The activators used were sodium silicate (SS) and sodium hydroxide (SH), while the molar concentrations of SH were varied at 12 M, 14 M, and 16 M. Moreover, mechanical properties, microstructural behaviour and mineralogical phases of the selected samples were examined. The results revealed that up to 40% CCA replacement level exhibited higher strengths than Portland cement concrete (PCC). Besides, a good relationship exists between the experimental results and the proposed model equations. These proposed models can be beneficial in the development of the strength design of GPC and PCC incorporating agro-industrial wastes. Furthermore, the study shows the possibility of incorporating CCA with GGBFS for production of GPC and the tenability of curing GPC at ambient conditions for the structural application was also attained.